Analysis and Applications of Quantile Approach on Residual Extropy (Statistics, Optimization & Information Computing, 2023)
Extropy is a measure of the uncertainty of a random variable. Motivated with the wideapplicability of quantile functions in modeling and analyzing statistical data, in this paper, we studyquantile version of the extropy from residual lifetime variable, "residual quantile extropy" in short.Unlike the residual extropy function, the residual quantile extropy determines the quantile densityfunction uniquely through a simple relationship. Aging classes, stochastic orders and characterizationresults are derived, using proposed quantile measure of uncertainty. We also suggest some applicationsrelated to (n i + 1)-out-of-n systems and distorted random variables. Finally, a nonparametricestimator for residual quantile extropy is provided. In order to evaluate of proposed estimator, we usea simulation study.